No alternative to austerity: how BBC broadcast news reported the deficit debate. (September 2016) - Berry, Mike
This article examines how BBC News at Ten covered the emergence of the UK public deficit debate in 2009. A total of 25 days of coverage drawn from the first seven months of 2009 were subject to a source and thematic content analysis to examine how news bulletins explained the emergence, consequences and possible solutions to the rise in the public deficit. Results indicated that political and financial elites dominated coverage. The consequence was that the news reproduced a very limited range of opinion on the implications and potential strategies for deficit reduction. The view that Britain was in danger of being abandoned by its international creditors with serious economic consequences was unchallenged and repeatedly endorsed by journalists. Despite their limited record of success during recessions, austerity policies dominated discussion of possible solutions to the rise in the deficit. This research thus raises questions about impartiality and the watchdog role of public service journalism.